The Effect of Direct Thermal Method, Temperature and Time on Microstructure of a Cast Aluminum Alloy - Asnul Hadi, Ahmad; Naher, S.; Brabazon, D. (Taylor & Francis, 2014)
The direct thermal method is used for the creation of globular microstructures suitable for semi-solid metal forming. In this paper, both simulation and experimental results using direct thermal method are presented. ProCAST® software was used to estimate temperature distribution inside the aluminum billet. In validation work, molten aluminum A356 was poured into metallic copper tube molds and cooled down to the semi-solid temperature before being quenched in water at room temperature. The effect of pouring temperatures of 630°C, 650°C, 665°C, 680°C and holding times of 45s and 60s on the microstructure of aluminum A356 alloy were investigated. The simulation results showed that the average temperature rate within the copper mold, from initial pouring temperature to just before quenching, was approximately 1°C/s. Examination of the solidified microstructures showed that the microstructure was more spherical when lower pouring temperatures and holding periods were used. From the micrographs it was found that the most globular and smallest structures were achieved at processing parameters of 630°C and 45s.